Seismic resilient design with base isolation device using friction pendulum bearing and viscous damper - Chen, Xu; Xiong, Jianfeng (Soil dynamics and earthquake engineering (1984), 2022)
This paper proposes an improved base isolation device to achieve seismic resilient design of structures during earthquakes, which is composed of conventional friction pendulum bearing (FPB) and viscous damper (VD) and named as FPB-VD. The formulation and equation of motion of this device is first presented, and its efficiency is then verified through comparing seismic responses obtained from finite element models. The results show that compared with the prototype system without any isolation approach and that with conventional FPB, this proposed FPB-VD device is quite efficient in reducing both the structural acceleration and deformation demands. Besides the mean values of seismic demands, the dispersion caused by randomness and types of input motions could be substantially suppressed as well, which improves the predictability of structural performance and is significant in engineering practice. Additionally, extensive parametric analysis reveals that the optimal design parameters of FPB-VD are influenced by both the input intensities and types of ground motions, which should be carefully determined to achieve balance between various aspects. •Propose base isolation device (FPB-VD) composed of friction pendulum bearing (FPB) and viscous damper (VD).•FPB-VD effectively reduces the structural acceleration and deformation, as well as response dispersions.•FPB-VD outperforms FPB in significantly reducing excessive deformation of isolation layer.•Suggestions are proposed and validated for selection of design parameters of PFB-VD through parametric analyses.